Inflation Targeting in the Context of IMF-Supported Adjustment Programs - Schwartz, Gerd (IMF Working Papers; Working Paper, 2001)
This paper argues that the IMF's traditional monetary conditionality-a ceiling on net domestic assets of the central bank and a floor on its net international reserves-should be adapted in IMF-supported adjustment programs with countries which have a framework of explicit inflation targets for the implementation of monetary policy. This adaptation should aim at enhancing correspondence and consistency between the monetary objectives of the central bank and the targets established under the IMF-supported adjustment program, as well as between the different instruments used to achieve the policy objectives and targets. The paper reviews various general options in this regard, and, using the case of Brazil as an example, demonstrates how these options may be implemented in practice.